ANALISIS SUASANA KAFE DAN GAYA HIDUP TERHADAP KEPUTUSAN BERKUNJUNG PADA KAFE BERBASIS HOTEL - Reni Uniana; Asep Muhamad Ramdan; Dicky Jhoansyah (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2023)
Today the cafe business is increasingly everywhere, because the cafe business has also penetrated the hospitality industry. Z generation is the largest population in Indonesia. Eating and drinking outside activities occupy the fifth position from the allocation of z generation funds. The problem in this study is the price offered by hotel-based cafes which is quite expensive for z generation in Sukabumi City. This study is to determine the effect of café atmosphere and lifestyle on visiting decisions. This study uses multiple linear regression data processing techniques. The sample of this study are 383 people from z generation who had visited a cafe based on data collection via a Google questionnaire using cluster sampling techniques. The results of partial testing (t-test) of two independent variables the atmosphere of the cafe and lifestyle, each of which has a significant positive influence on the decision to visit. Simultaneous test results show that the atmosphere of the cafe and lifestyle together influence purchasing decisions. The coefficient of determination show that the cafe atmosphere and lifestyle contribute 11.7649% to visiting decisions while the remaining 88.2351% can be influenced by other variables except in this study.